Transformation of Business Models in Spa Enterprises for Medical Purposes in Situations of Epidemic Threats - Adam R. Szromek (Journal of Open Innovation: Technology, Market and Complexity, 2021)
The suspension of tourism due to the COVID-19 pandemic has led to an almost complete halt in the activities of the tourism industry. This paper attempts to assess the ability to use the potential of health tourism enterprises in counteracting the SARS-CoV-2 virus pandemic and to propose a sustainable transformation of the business model of the health tourism enterprise, taking into account the determinants of sustainable tourism and health crises. The author presents the results of research conducted in March 2021 among 19 managers of the largest spa enterprises in Poland. The managers’ experiences from the first year of the COVID-19 pandemic indicate that sanatoriums and other health tourism facilities, during periods of health and humanitarian crises, can successfully play a preventive and relieving role for healthcare facilities by implementing post-COVID treatment, conducting vaccinations, organizing isolators for people in quarantine, and even treating patients who do not have symptoms but require hospitalization. The transformation of the business model of these companies, in the form of a sustainable SusHT-CANVAS+ business model, is proposed and the mentioned critical activities are positioned in the model in the form of sustainable value.